Storage stability of refrigerated vacuum-packed and heat-sealed baye-baye - Sasana, Mark Jan Cadiz (2006.)
The storage stability of refrigerated vacuum-packed (T1) and heat-sealed (T2) baye-baye was investigated by monitoring the changes in their physico-chemical and microbiological properties and their sensory attributes during storage.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Storage; Baye-baye -- Refrigerated vacuum-packed.; Baye-baye -- Heat-sealed.